The next deadly chapter - Burns, V. M., 1964- (Burns, V. M., 1964- Mystery bookshop mystery., 2025)
"All Sam wanted was to make a good impression on her fiancé Frank's mother, the very proper Dr. Camilia Patterson. But when Nana Jo and the lively ladies of Shady Acres Retirement Village throw a surprise bridal shower for Sam at the Four Feathers Casino--watch out! Things spin out of control faster than a roulette wheel. Fortunately, Sam knows when to fold 'em and slips back to her room to work on her latest historical mystery set between the wars, in which a houseguest meets a grim end at an English country manor. The morning after brings another rude surprise. Sam gets a frantic call from Camilia, who's discovered a dead body in her room. Now winning over her soon-to-be mother-in-law means keeping the good doctor out of a potential scandal and attempting to discreetly solve a murder without ruffling any feathers. For that she'll need the help of Nano Jo--not exactly the soul of discretion--Detective "Stinky" Pitt, and the ladies--because the casino killer keeps upping the ante ..."--